A epistemologia em Freire e sua relação com o currículo da cidade de Sorocaba - Bertanha, Adriano (Universidade Federal de São Carlos, 2018)
This study originated from the perception that some productions that are linked to Paulo Freire's pedagogical perspective do not appear to be related to their theoretical foundations and their political-pedagogical objectives. From this perception came the problem of this research, which confronts Freirean epistemology with the official Sorocaba curriculum, since the supporting documents claim to be based on Freir-ean foundations, whose episteme is significantly exposed in the works "Pedagogy of the oppressed" (1987) and "Extension or Communication?" (1983), of this author. With this finding, we ask ourselves which are the main epistemological references that support that curriculum, and what implications they cause in the systematization of those documents. For this reason, the general bibliographic review was followed, beginning with the visit to the above quoted author's works, cutting important pas-sages to determine the freirean categories that served as tools for the analysis of the document, and which were compared with excerpts from the works of thinkers of phenomenology and Marxism, mainly with whom Freire demonstrated proximity, in order to detect influences arising from it. The following is a list of the documents that underpin the Sorocaba curriculum: the 2016 Reference Framework, which reflects the theoretical basis of the 2012 Curricular Matrix, which is based on contents and practices that determine the subjects of the serial, to detect if these, claiming to fol-low the work of Freire, are committed to its foundations and political objectives. It should be noted that Freire appropriates primary concepts of existential phenome-nology, from which education derives as a political act, in addition to demonstrating convergence with Marx's thoughts, culminating in the categories of dialogue and political commitment as a humanizing practice; these the knowledge that served as tools of analysis for the documentary stage of the work. As a result, it was found that the Referential Framework brings perspectives and quotes from progressive authors close to the Freirean proposal and even cites them directly, but the content and prac-tical issues of the Curriculum Matrix are based on different political-pedagogical ob-jectives.
Keywords: Matriz curricular sorocabana; Currículo freireano; Epistemologia marxista; Freire, Paulo - 1021-1997; Currículos - Avaliação; Curriculum evaluation; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO